Role of Head Master of Secondary Schools on Effective Science Teaching: A Study in Darrang and Udalguri District (International Journal of Scientific Research and Management (IJSRM), 2022)
Head masters of schools are considered essential part in education system to impact teachers’ teaching commitment to improve classroom instruction for attaining quality education. This demanded the need of this study to investigate role of head master of secondary schools on effective science teaching at Darrang and Udalguri district. The study was guided by descriptive survey method. This study explores supervision quality of head masters and science teachers’ perceptions of effective science teaching for the improvement of classroom instruction. The study was carried out from a population of secondary schools in Darrang and Udalguri district of Assam. A purposive sample of 40 head masters and 120 science teachers selected from 70 secondary schools from two districts of the state was used for the study. A research instrument tagged self- prepared questionnaire was used to elicit information from the teachers and head masters. The findings further showed that the classroom instruction is improved by the continuous supervision and monitoring of Head master of secondary schools. The effective of science teaching also impact by the supervision of Head master